Recurrent or first preeclampsia in multiparae: A case-control study of singleton pregnancies in Reunion Island. (September 2019) - Tran, Phuong Lien; Robillard, Pierre-Yves; Dumont, Coralie; Schweizer, Chloé; Omarjee, Asma; Iacobelli, Silvia; Boukerrou, Malik
Abstract: Recurrent or first preeclampsia in multiparae : a case-control study of singleton pregnancies in Reunion Island Phuong Lien Tran, Pierre-Yves Robillard, Coralie Dumont, Chloé Schweizer, Asma Omarjee, Glorianne Lazaro, Silvia Iacobelli, Malik Boukerrou Objective: To compare multiparous women with a first occurrence of preeclampsia and those with recurrent preeclampsia in singleton pregnancies. Study design: a 17.5-year (2001–2018) case-control study conducted in the University's maternity of South Reunion (Indian Ocean), comparing 125 patients with recurrent preeclampsia and 742 patients with a first episode of the disease (controls). Statistical analyses were performed with use of the Student t -test for comparison of continuous data and the Chi-square or Fisher exact test for comparison of categorical variables. Results: There was no difference between the two groups concerning socio-demographic characteristics, post-partum haemorrhage, perinatal mortality rates. Nevertheless, recurrent preeclamptic women had a higher risk to present with prior chronic hypertension (OR 2.05 [1.30–3.23], p = 0.002), and to experience an early onset preeclampsia (< 34 weeks) compared to controls (OR 1.69 [1.15–2.48], p = 0.007). Women with recurrent preeclampsia were more prone to have C-sections (OR 1.63 [1.06–2.51], p = 0.024) mainly because of maternal indications (89.2% vs 76.4%, p = 0.008). Newborns from recurrent preeclampsia were more likely to have very low birthweight < 1500 g (OR 1.79 [1.16–2.77], p = 0.001), while there was no significant difference for gestational ages (34.1 vs 34.7 weeks). Conclusion: Recurrent multiparous preeclamptic women presented more severe maternal disease (with a higher rate of early onset preeclampsia). Persistent hypertension in women with a history of preeclampsia is a risk factor for developing recurrent preeclampsia, and these patients should be monitored more closely.